Estudo fitoquímico e atividade antioxidante de Zornia brasiliensis - Nascimento, Yuri Mangueira do (2016)
Zornia presents around 80 species distributed throughout the world, having representatives in Oceania, America, Africa and Asia, and this genus belongs to Leguminosae family. The species studied, Zornia brasiliensis, popularly known as "urinaria", "urinana" and "carrapicho" and has popular use reported as diuretic and for treatment of venereal diseases, it is distributed in various states of Brazil, is abundant in the Northeast. Thus, this study aims to contribute to the expansion of the chemical knowledge of genus Zornia through phytochemical study Zornia brasiliensis Vogel, and to evaluate the antioxidant activity and quantify the total phenolic. To perform the study, the plant material, dried and pulverized, was subjected to extraction and then to chromatographic procedures for isolation and purification of the chemical constituents. The elucidation of the chemical structures was determined by Nuclear Magnetic Resonance 1H, 13C and bidimensional comparisons with literature data. The chromatogram fractionation of the fraction ethyl acetate-methanol 10% resulted in the isolation of glycosylated isoflavonoid: ononin, the ethyl acetatemethanol 50% fraction was obtained a cyclitol: D-pinitol, and two glycosylated flavones: the isoorientin and isovitexin. Exception ononin, the compounds are isolated for the first time in Zornia genus. The antioxidant activity of the crude ethanolic extract (CEE) and dichloromethane fractions, ethyl acetate, ethyl acetate- methanol 10%, ethyl acetate-methanol 50% were checked by the method of sequestering radical DPPH (1,1-diphenyl-2-picryl -hidrazil) and the quantification of total phenolics (Folin-Ciocalteu), compared with the results obtained with the standards, ascorbic acid and gallic acid, respectively. The study of antioxidant activity showed greater activity fractions of ethyl acetate, ethyl acetate-methanol 10% and CEE, a result that can be associated with the fact that these fractions have shown the highest levels of phenolic compounds entres tested fractions, and the dichloromethane fraction presented higher EC50 and lowest concentration of phenolic compounds. Therefore, phenolic compounds can probably be responsible for the best results of antioxidant activity obtained by the test kidnapping of DPPH radical. The phytochemicals results reported in the literature show that the phenolic fraction isolated in dichloromethane not have the structural determinants responsible for this activity corroborating the results of this study.